![(\frac{x + 1}{x} ) ^{2} \\ = \frac{ {(x + 1)}^{2} }{ {x}^{2} } \\ = \frac{ (x + 1)(x + 1) }{ {x}^{2} } \\ = \frac{ {x}^{2} + 2x + 1}{ {x}^{2} }](https://tex.z-dn.net/?f=%20%28%5Cfrac%7Bx%20%2B%201%7D%7Bx%7D%20%29%20%5E%7B2%7D%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B%20%7B%28x%20%2B%201%29%7D%5E%7B2%7D%20%7D%7B%20%7Bx%7D%5E%7B2%7D%20%7D%20%20%5C%5C%20%20%3D%20%5Cfrac%7B%20%28x%20%2B%201%29%28x%20%2B%201%29%20%7D%7B%20%7Bx%7D%5E%7B2%7D%20%7D%20%5C%5C%20%3D%20%5Cfrac%7B%20%7Bx%7D%5E%7B2%7D%20%20%2B%202x%20%2B%201%7D%7B%20%7Bx%7D%5E%7B2%7D%20%7D%20)
Hope you could get an idea from here.
Doubt clarification- use comment section.
Answer:
g(x) = |x-3| -4
Step-by-step explanation:
to shift right by 3, subtract three from x inside the absolute value.
to shift down by 4, subtract 4 outside of the absolute value.
g(x) = |x-3| -4
Answer:
219 + 159 <= x <= 369 + 309
378 <= x <= 678
Step-by-step explanation: